2020
DOI: 10.21203/rs.3.rs-56419/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Beneficial Effects of Square Dance on Musculoskeletal System in Early Postmenopausal Chinese Women: A Cross-sectional Study.

Abstract: Background: This study was set to investigate the beneficial effects of square dance on musculoskeletal system of early postmenopausal Chinese women.Methods: Chinese postmenopausal women, who had been without menstruation for 1 to 10 years from the onset of menopause were recruited from community centers for this study. A standardized structured face-to-face interview was performed to collect demographic information, life styles, personal medical history, diet and menstrual status. Subjects who had been practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Most of our surveys began after the COVID-19 pandemic, so the number of people gathering for square dancing may have decreased. However, our preliminary findings suggested that square dancing, which was beneficial for the musculoskeletal system [30] and incorporated the pleasurable experience of social communication [31] and musical rhythm [32], may provide greater cognitive protection with less time spent exercising and thus could be regarded as a recommended method of LTPA for elderly individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Most of our surveys began after the COVID-19 pandemic, so the number of people gathering for square dancing may have decreased. However, our preliminary findings suggested that square dancing, which was beneficial for the musculoskeletal system [30] and incorporated the pleasurable experience of social communication [31] and musical rhythm [32], may provide greater cognitive protection with less time spent exercising and thus could be regarded as a recommended method of LTPA for elderly individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Research indicated that square dancing could significantly improve the participants' family cohesion and subjective well-being. Moreover, square dancing has been shown to significantly reduce the risk of coronary heart disease in older adults [24] and increase the lower limb muscle strength and single-leg balance [25].…”
Section: Introductionmentioning
confidence: 99%
“…Dance sports [15], Pilates [16], yoga [17], and resistance exercise [18] are all exercises that improve the physical health of postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%